Design optimization of low-power high-performance DSP building blocks - Gemmeke, T.; Gansen, M.; Stockmanns, H.J.; Noll, T.G. (IEEE journal of solid-state circuits, 2004)
In recent years, power dissipation along with silicon area has become the key figure in chip design. The increasing demands on system performance require high-performance digital signal processing (DSP) systems to include dedicated number-crunching units as individually optimized building blocks. The various design methodologies in use stress one of the following figures: power dissipation, throughput, or silicon area. This paper presents a design methodology reducing any combination of cost drivers subject to a specified throughput. As a basic principle, the underlying optimization regards the existing interactions within the design space of a building block. Crucial in such optimization is the proper dimensioning of device sizes in contrast to the common use of minimal dimensions in low-power implementations. Taking the design space of an FIR filter as an example, the different steps of the design process are highlighted resulting in a low-power high-throughput filter implementation. It is part of an industrial read-write channel chip for hard disks with a worst case throughput of 1.6 GSamples/s at 23 mW in a 0.13-/spl mu/m CMOS technology. This filter requires less silicon area than other state-of-the-art filter implementations, and it disrupts the average trend of power dissipation by a factor of 6.